Digitalization in the transformation of the business environment - Butryn, Beata (Cyfryzacja w transformacji środowiska biznesowego, 2020)
The business environment is inextricably linked with the ongoing globalization process, which is currently stimulated by the dynamic development of ICT. The result of these dependencies is the digitization of the transformation of the business environment. The article discusses the issues related to globalization, which creates a new system of dependencies in the business environment, and the impact of digitization was presented, indicating that it is a key factor in the transposition of business processes. Modern technologies are changing the way business is managed, by setting new frameworks for cooperation opportunities, they shape strategies, organizational structures, and above all contribute to the development of new business models. The considerations lead to the achievement of the goal of indicating the growing importance of digitization in changes in the business environment. The increase in importance has significantly accelerated in the era of events related to the COVID-19 coronavirus pandemic. This article used the author’s own research, literature studies, Internet sources, comparative analysis, and the logic of inference
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 4 (58), s. 67-79
Keywords: informatyka ekonomiczna